Electromagnetic analysis of ohmic quality factor of corrugated coaxial cavity structure for MILO - Kumar A.; Tripathi P.; Dwivedi S.; Jain P.K. (My University, 2025)
Corrugated coaxial cavity structures are used as slow wave structure for magnetically insulated line oscillator (MILO). The dispersion relation for electromagnetic wave propagation through different corrugated coaxial cavity structure has been calculated analytically and validated through simulation. Electromagnetic wave propagation through different structures has been estimated through commercial simulation software, 'CST Microwave studio'. Furthermore, the electromagnetic analysis has been used to estimate the ohmic quality factor for different corrugated coaxial cavity structure. The results obtained through analysis compared with the simulation results and found with ~5% variation. The ohmic quality factor and EM wave propagation through different structures helps us to select the optimal corrugation coaxial cavity structure for MILO device. © 2020 Indian Radio Science Society.